Implementasi Rekam Medis Elektronik Terhadap Kepuasan Pasien di Puskesmas Linggar - Intan Ali Sopian; Erix Gunawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to investigate the impact of implementing electronic medical records (EMRs) on patient satisfaction at Puskesmas Linggar. The study has two main objectives. First, to examine the implementation electronic medical records and second to assess the level of patient satisfaction resulting from this implementation. This research employs a quantitative, descriptive approach. Based on the result and discussion presented, it can be concluded that the implementation of electronic medical records has a significant positive impact on patient satisfaction at the Linggar Health Centre, with a satisfaction rate of 91,6%. This indicates that the implementation medical records (EMRs) positively affects patient satisfaction.